Guía docente para desarrollar la lectoescritura en niños y en niñas de primeroy segundo año de Educación General Básica, desde el enfoque comunicativo de la lengua. - Diaz Negrete, Gissela Estefania (2014)
The writing process is critical to the communicative act of human beings as it allows humans to interact with each other, thus it is present in all aspects of life. From an educational perspective reading and writing are the starting point for understanding of academic areas. For this reason, we have taken into account the physical, emotional, cognitive characteristics of the students since this characteristics are involved in the focus area of students. Including the steps of reading and writing to work them better in the classroom and get significant results based on constructivism and the communicative approach where children are the principal author of his knowledge